Role of Mg ions in modulating the morphology and structure of CaCO3 crystals grown in aqueous foams - Rautaray, Debabrata; Kasture, Manasi; Sastry, M. (CrystEngComm, 2005)
We investigate the role of magnesium ions in modulating the morphology and crystallography of CaCO3 crystals grown in aqueous foam. This is accomplished by first making foams from an aqueous mixture of CaCl2+MgCl2 and the anionic surfactant aerosol-OT (AOT) followed by reaction of the foam with Na2CO3 solution. The Ca2+ and Mg2+ ions electrostatically complex with AOT and react with Na2CO3 within the foam to yield CaCO3 crystals of interesting morphology. These studies indicate that CaCO3 in a fractured, needle-like morphology was formed at high Mg2+ concentrations in the foam whereas porous, rhombic CaCO3 crystals were obtained at low Mg2+ concentrations. The effect of water drainage time and thereby, the structure of the foam on the morphology of the CaCO3 crystals grown was also studied.

Synthesis of CdS and alloyed CdMnS nanocrystals using aqueous foams - Kumar, P. Senthil; Kasture, Manasi; Raghavan, U; Pasricha, R; Sastry, M (Journal of Nanoscience and Nanotechnology, 2005)
Certain surfactant-stabilized aqueous foams provide a potentially efficient and simple chemical route for the synthesis of various nanomaterials with controllable structure, size, and shape. In the present work, a one-step process for the synthesis of CdS and Cdl(1-x)Mn(x)S (0 < x < 10) nanocrystals has been described. Aqueous CdCl2 and the aerosol-OT solutions are homogeneously mixed together and thereafter, nitrogen is bubbled through this solution to produce stable aqueous foam. After drainage of the foam, the freestanding dry foam consisting of cadmium cations electrostatically complexed with the anionic aerosol-OT molecules at the liquid-gas interface is treated with H2S vapor. The foam turns yellowish-orange and collapses, in the process yielding CdS nanoclusters of variable morphology. This morphology variation is appropriately attributed to growth of the CdS as well as alloyed Cd1-xMnxS nanoparticles in different regions of the foam contributing to the varying topological structure. Optical absorption spectra of both CdS and Cd1-xMnxS nanoparticles clearly show a well-defined exciton absorption feature around 450 nm due to quantum confinement effects. The interesting band edge emission characteristics of these AOT-capped CdS and Cd1-xMnxS nanoparticles produced in the foam are discussed with respect to their size and shape. Particular interest in the present novel aqueous foam approach arises due to the fact that the cubic zincblende CdS and alloyed Cd1-xMnxS nanocrystals could easily be obtained even under ambient experimental conditions itself.
Keywords: absorption and fluorescence; aerosol-OT; alloyed CdMnS nanocrystals; aqueous foams; CdS nanoclusters; quantum confinement; zincblende

Synthesis of gold, silver and their alloy nanoparticles using bovine serum albumin as foaming and stabilizing agent - Singh, A. V.; Bandgar, B. M.; Kasture, Manasi; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Materials Chemistry, 2005)
A simple and convenient method for the synthesis of gold, silver and their alloy nanoparticles in a foam matrix using the protein bovine serum albumin (BSA) is reported. BSA is an excellent foaming agent and, by virtue of its zwitterionic character at the protein isoelectric point, may be used to bind to either cationic silver (Ag+) or anionic gold (AuCl4-) ions in the foam. The metal ions in the foam are thereafter reduced in situ to yield silver and gold nanoparticles. The versatility of an amphoteric foaming agent is further demonstrated by the simultaneous binding of Ag+ and AuCl4- ions with zwitterionic BSA leading to the possibility of obtaining Au-Ag alloy nanoparticles in the foam. The BSA molecules coat and stabilize the nanoparticles thus prepared eliminating the necessity of employing an additional stabilizing agent in the experimental recipe.

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Halide ion controlled shape dependent gold nanoparticle synthesis with tryptophan as reducing agent: enhanced fluorescent properties and white light emission - Kasture, Manasi; Sastry, Murali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2010)
We report the synthesis of Au nanoparticles in presence of two surfactants cetyltrimethyl ammonium chloride (CTAC) and cetyltrimethyl ammonium bromide (CTAB) by reducing Au(3+) ions with tryptophan. Interestingly, triangular shaped particles were seen to form in presence of CTAB, while spherical nanoparticles resulted with CTAC. The highlight of this result is the white light emission from the Au triangles obtained when CTAB is used. These results are supported by lifetime measurements and fluorescence. (C) 2009 Elsevier B. V. All rights reserved.

Investigation of magnetic anisotropy in Co nanoparticles using ferromagnetic resonance technique - Sendilkumar, A.; Kasture, Manasi; Patel, Pitamber; Ramana, Chepuri V.; Bhagavatula L. V. Prasad; Srinath, S. (Journal of Physics: Conference Series, 2010)
Using ferromagnetic resonance (FMR) technique, we have investigated the temperature dependence and angular dependence of line width and resonance magnetic field of Co nanoparticles capped with novel alkane carboxylic acids of varying chain lengths. The magnetic properties such as blocking temperature and anisotropy sensitively depend on the chain length as evidenced by the temperature dependence of line width. These results indicate that the magnetic properties of these samples are critically governed by the interparticle interactions which are decided by the chain length. The presence of anisotropy even up to very high temperature above the blocking temperature observed in these studies confirms the presence of inter-particle magnetic interactions as well as intra-particle exchange interaction between the core and shell regions as evidenced by our earlier ac susceptibility and transverse susceptibility measurements on similar system.

Detection of toxic metal ions Pb2+ in water using SiO2@Au core-shell nanostructures: A simple technique for water quality monitoring - Daware, Krishna; Kasture, Manasi; Kalubarme, Ramchandra; Shinde, Rakesh; Patil, Kashinath; Suzuki, Norihiro; Terashima, Chiaki; Gosavi, Suresh; Fujishim, Akira (Chemical Physics Letters, 2019)
The present paper demonstrates a development of simple, sensitive and selective optical probe for detection of Pb2+ ions in water using monodispersed silica-gold core-shell nanostructures (SiO2@Au NSs). Structural and elemental analysis confirms the phase purity of nanostructures. The SPR studies for SiO2 @Au NSs reveals, linear dynamic range for Pb2+ ions detection, in the concentration range of 100 ppb to 2 ppm, with detection limit of 100 ppb, which is 5 times higher than AuNPs. Cross sensitivity study confirm its selectivity towards Pb2+ ions over other metal ions. XPS analysis shows the interaction of Pb2+ ions with core-shell NPs.